Addressing Domestic Violence as It Relates to Livelihoods in Rural Tajikistan - Wood, Elizabeth A. (Violence against women, 2021)
This study investigates patterns of rural livelihoods in Khatlon Province, Tajikistan, as it relates to gender roles and responsibilities. This included a workshop in the train-the-trainer format for community workers to implement a violence participatory workshop among village-related women and men. Key informant interviews were performed to collect information about the perceptions of violence among village households followed by individual semistructured interviews with participants of the participatory workshops. Analysis included ethnographic content analysis using NVivo 12 software to extract salient themes. Results concluded that education and employment were essential in building empowerment among women in the villages.